The effect of building self esteem on aggressive behavior in Lebanese middle school female students - Tayara, Rana Mohamad Marwan (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2006)
The purpose of this study was to determine whether a self-esteem program implemented at the middle school level three times weekly during one academic se mester could reduce aggressive behaviors of female students. The two variables s tudied were self-esteem and aggressive behavior. One school, two grades and four sections were selected. The sample included 30 middle school female students 13 to 14-year old from grades 7 and 8 from one private school in Beirut. The instruments used were the Battle's Culture-Free Self-Esteem Inventory second edition (CFSEI-2) (Battle, J, 1992) and the Buss and Perry 1992 Aggressi on Questionnaire. For the intervention, the Building Self-Esteem program by R.W, Reasoner and G.S, Dusa, (1991) was chosen. The rating scales were administered in English. The data obtained were analyzed using the SPSS for windows. Students ' responses were reported and compared using ANCOVAs and t-tests. Results showed a significant increase in self-esteem and a significant de crease in aggression for female students post intervention. The ANCOVAs also sho wed a significant difference between the control and the experimental group on a ggression and self-esteem post intervention. Based on these results, implication and suggestions for further research were drawn.
: Mémoire
Keywords: Cycle moyen; Education des filles; Estime personnelle; Female education; Intermediate Education; Self-Esteem